Comparative Analysis of the Blowfish Algorithm and the Des Algorithm in the Document File Encryption and Decryption Process - Ronaldo Praja Saputra; Jusuf Wahyudi; Juju Jumadi (Jurnal Komputer, Informasi dan Teknologi, 2022)
Security issues are one of the most important aspects in the world of information technology, such as document security. Most of the documents are created through the Microsoft Office application package, because it is easy to use. There are several applications available in Microsoft Office, namely Microsoft Word, Microsoft Excel, Microsoft Access, Microsoft Powerpoint, and others that are used to process words and numbers according to user needs. Comparative analysis of the Blowfish algorithm and the DES algorithm in the encryption process is carried out based on 3 comparison aspects, namely processing time, file size and memory used. Comparisons were made with 40 test data in the form of document files, each consisting of 10 test data with extension formats *.docx, *.xlsx, *.pdf, and *.pptx, where these formats are familiar in data processing using Microsoft Office. Based on the tests that have been carried out, it can be concluded that in the encryption process, the DES Algorithm has a faster time than the Blowfish Algorithm with a percentage of the DES Algorithm's encryption processing time of 3.7975%. In the decryption process, the DES Algorithm has a faster time compared to the Blowfish Algorithm with a percentage of the DES Algorithm's encryption processing time of 3.595%. In the encryption process, the file size in the DES Algorithm increases bytes less than the file size in the Blowfish Algorithm. In the decryption process, the file size in the DES Algorithm and the Blowfish Algorithm does not change, because the file size returns to the original file size. In the encryption process, the DES Algorithm uses less memory compared to the Blowfish Algorithm with the percentage of memory used by the DES Algorithm being 49.655%. In the decryption process, the Blowfish Algorithm uses less memory compared to the DES Algorithm with the percentage of memory used by the Blowfish Algorithm 49.5925%